Thaumarchaeal and sterol data at monthly to quarterly resolution from Santa Barbara Basin sediment via mass spectrometry imaging - Susanne Alfken; Lars Wörmer; Julius S Lipp; Tiffany J Napier; Marcus Elvert; Jenny Wendt; Arndt Schimmelmann; Kai-Uwe Hinrichs (PANGAEA, 2021)
Molecular biomarker data from isoprenoidal tetraethers from planktonic archaea and C29 sterols measured with the extraction-free approach of MALDI FT-ICR-MS in annually varved sediments from the Santa Barbara Basin deposited from AD 1900 - 2009.